Ayurvedic Review On Vibandha in Pediatric Age: Life Sciences -Ayurveda - Borse, Ruchi Jaywant; Rathi, Renu; Pawade, Sachin; Thakre, Trupti (International Journal of Life Science and Pharma Research, 2023)
Constipation is a disease condition resembling Vibandha or Badhapurish described in Ayurveda. Vibandha is a commoncondition seen in childhood and one of the main reasons for increased parental concerns. It presents with the difficulty child facesin defecation associated with hard stools and infrequent bowel movements. The peak incidence of constipation in the Pediatricage group is at 2–5 years of age. Most children report constipation due to Hetus like Vata Dushita Stanya Sevana, Krimi, Parish Vega-Vidharana, etc. It leads to the vitiation of Samprapti Ghatak like Amotpatti, Vata Prakopa, and Jatharagni Mandya, which ultimatelycauses Vibandha to the child. Vibandha has various complications like Chardana, Rasa Kshaya, Karshya, etc. Constipation is easier toprevent than to treat by following maintenance with adequate exercise, fluid intake, and a high-fiber diet. The treatment of Vibandhaincludes Nidan Parivarjana and Dipan, Pachan Anulomana, Bhedana, Rechana, etc. Here one attempt is made to introduce Vibandhaas a disease in children. The main objectives are to introduce Vibandha as a disease by detailing Nidan Panchak, especially the Rupa,Samprapti, etc., and to establish a missing link between them.